Malvina, or Spoken and Written Word in the Novel - Szary-Matywiecka, Ewa (Karolinum Press, 2022)
This study by Szary-Matywiecka presents Malvína, or the Heart’s Intuition by Maria Wirtemberska, the first Polish psychological novel, as a work worth of critical attention. Despite its didactic message about the superiority of the heart over the mind, the work met with early success. The study deals with several aspects of the novel, while making use of methods developed by structuralists and formalists, including Michał Głowiński’s concept of formal mimesis. At the same time, it relies on current theories on language and proves that Malvína is not merely a sentimental book. The novel makes use of the traditional motif of twins separated at birth who finally meet many years later, and captures a picture of society of that time in Warsaw. The plot is permeated by the theme of doubling, two main male characters, double literary energy, and the double self of Wirtemberska as both the narrator and author.